Research on Pressure Drop in the Accelerate Zone of Horizontal Conveying of Concrete Spraying. (23rd December 2019) - Ma, Guanguo; Liu, Zhaoxia; Gong, Xiaobing; Chen, Lianjun; Liu, Guoming; Pan, Gang; Dong, Qizheng
Abstract : A pressure transmitter was installed at a specific position in a concrete conveying line to disclose the pressure drop when compressed air was conveyed during concrete spraying. A statistical analysis of the pressure at different positions was undertaken. Experimental results demonstrated that in the accelerate zone of horizontal conveying of concrete in the line, the pressure drop mainly occurred during the acceleration, collision, and friction processes. The momentum equation was introduced during the experiment, which interpreted the pressure drop caused by the accelerated conveying of concrete. The theoretical equation was corrected based on the results of theoretical experiments by introducing the value of α, and the experimental results were then optimized, thus obtaining an approximate model of pressure drop during the conveying of concrete. In addition, experimental results were compared with a model equation that showed the reliability of the proposed model. Research conclusions are of great significance to regulate the pressure drop in the conveying line of concretes, to design working parameters of concrete spraying devices, and to predict the ultimate distance for the conveying of concrete.